2012
DOI: 10.11113/jt.v54.87
|View full text |Cite
|
Sign up to set email alerts
|

Review On Lean Principles For Rapid Construction

Abstract: Penggunaan prinsip “lean” di dalam proses pembinaan adalah untuk melancarkan perjalanan proses pembinaan terutamanya di tapak binaan dengan mengurangkan aktiviti–aktiviti yang tidak penting untuk melengkapkan kitaran pembinaan secara efektif. Tujuan prinsip ini diadaptasi di dalam pembinaan yang pantas adalah untuk menyelesaikan masalah yang kompleks disebabkan oleh susunan aktiviti yang padat di dalam proses pembinaan itu sendiri. Lima prinsip utama “lean” telah disesuaikan dengan kajian kes. Di dalam aplikas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The SLR is a method that was originally developed in medical sciences and was used in other fields including management. In this method, a comprehensive review on a specific topic and clear research question is done based on an explicit pre-determined method that Koskela et al (2002) "Lean is a way to way to design production systems to minimize waste of materials, time, and effort in order to generate the maximum possible amount of value" Diekmann et al (2004, p. 3) "A continuous process of eliminating waste, meeting or exceeding all customer requirements, focusing on the entire value stream and pursuing perfection in the execution of a constructed project" Yahya and Mohamad (2011) "Lean construction is about managing and improving the construction process to profitability deliver what the customer needs by eliminating waste in the construction flow due to construction contract, specification and agreement between client and other parties by using the right principle, resources, and measure to deliver things right first time" Marhani et al (2012) "Lean Construction is a concurrent and continuous improvement to the construction project by reducing waste of resources and at the same time able to increase productivity and secure a better health and safety environment in order to fulfill the client's requirements as well as contributing toward sustainable and greener environment" Abdelhamid ( 2013)…”
Section: Methodsmentioning
confidence: 99%
“…The SLR is a method that was originally developed in medical sciences and was used in other fields including management. In this method, a comprehensive review on a specific topic and clear research question is done based on an explicit pre-determined method that Koskela et al (2002) "Lean is a way to way to design production systems to minimize waste of materials, time, and effort in order to generate the maximum possible amount of value" Diekmann et al (2004, p. 3) "A continuous process of eliminating waste, meeting or exceeding all customer requirements, focusing on the entire value stream and pursuing perfection in the execution of a constructed project" Yahya and Mohamad (2011) "Lean construction is about managing and improving the construction process to profitability deliver what the customer needs by eliminating waste in the construction flow due to construction contract, specification and agreement between client and other parties by using the right principle, resources, and measure to deliver things right first time" Marhani et al (2012) "Lean Construction is a concurrent and continuous improvement to the construction project by reducing waste of resources and at the same time able to increase productivity and secure a better health and safety environment in order to fulfill the client's requirements as well as contributing toward sustainable and greener environment" Abdelhamid ( 2013)…”
Section: Methodsmentioning
confidence: 99%
“…However, current available scheduling methods could not achieve collaboration of stakeholders due to the nature of multiparty involvement agreement. Yahya and Mohamad (2011) identified lean principles to reduce nonvalue adding activities through team collaboration's planning effort. Similarly, Kovvuri et al (2016) also found that last planner benefits construction time reduction, quality, cost improvement, build trust, and increase coordination.…”
Section: Application Of Scheduling Methodsmentioning
confidence: 99%
“…Last Planner System (LPS)) has been widely studied to improve performance of project scheduling. For example, (Yahya & Mohamad, 2011) studied how to apply lean for rapid work flow. The technique is applied to solve CPS constraints via team collaboration (Alsehaimi et al, 2014;Daniel et al, 2017;Kovvuri et al, 2016); -CPS planning and management: CPS planning and controlling of CPS has been examined.…”
Section: Science Mapping Of Co-occurrence Of Abstractmentioning
confidence: 99%
“…This management approach has been introduced by Koskela [8], which is emphasised on eliminating construction wastes. Yahya and Mohamad [9] added LC is likely on managing and improving the construction processes. LC also capable of fulfilling the client's needs as well as contributing towards a sustainable and greener environment [10].…”
Section: Introductionmentioning
confidence: 99%